147k views
2 votes
PLEASE HELP ASAP 70 POINTS

question 1) D = {[x, f(x)]: (-1, 3), (0, 2), (1, 3), (2, 6), (3, 11)} Write the rule for f(x).



question 2) Given: F(x) = 3x 2 + 1, G(x) = 2x - 3, H(x) = x

F(-2) =




question 3) Given: F(x) = 3x 2 + 1, G(x) = 2x - 3, H(x) = x

F(x) + G(x) =

2 Answers

6 votes
i know number 2 only
PLEASE HELP ASAP 70 POINTS question 1) D = {[x, f(x)]: (-1, 3), (0, 2), (1, 3), (2, 6), (3, 11)} Write-example-1
User Aldeb
by
5.2k points
6 votes

question 1)

D = {[x, f(x)]: (-1, 3), (0, 2), (1, 3), (2, 6), (3, 11)} Write the rule for f(x).

when x = 0 , f(x) = 2

f(x) = x^2 + 2 ....this is the rule

question 2)

Given: F(x) = 3x^2 + 1, G(x) = 2x - 3, H(x) = x

F(-2) = 3(-2)^2 + 1 = 12 + 1 = 13

F(-2) = 13


question 3)

Given: F(x) = 3x 2 + 1, G(x) = 2x - 3, H(x) = x

F(x) + G(x) = 3x^2 + 1 + 2x - 3

F(x) + G(x) = 3x^2 + 2x - 2

User Pbhowmick
by
5.2k points